ACHIEVING LEARNING OUTCOMES IN TEACHING BOTANY - Khujanazarov U.E., Khujanazarov U.E.; Saidmuratov Sh.Kh, Saidmuratov Sh.Kh (Actual problems and prospects of the study of the fauna, 2024)
Today, it is important to study systematics of botany and use innovative technologies to create knowledge and skills in students. However, the role of case technologies in the ability to use modern technologies from the point of view of science and effectively achieve educational results is incomparable.